Baseline neutrophil-to-lymphocyte ratio and c-reactive protein predict efficacy of treatment with bevacizumab plus paclitaxel for locally advanced or metastatic breast cancer - Miyagawa, Yoshimasa (Oncotarget, 2020)
The effect of bevacizumab plus paclitaxel therapy on progression-free survival (PFS) is prominent; however, no overall survival (OS) benefit has been demonstrated. Our aim was to study the predictive efficacy of peripheral immune-related parameters, neutrophil-to-lymphocyte ratio (NLR), absolute lymphocyte count (ALC), and c-reactive protein (CRP) in locally advanced and metastatic breast cancers. A total of 179 patients treated with bevacizumab plus paclitaxel were recruited from three institutes in the test cohort. The cut-off values of NLR, ALC, and CRP were set at 3, 1500/μL, and 1.0 mg/dL, respectively, and baseline values of these factors were measured. The PFS of patients with NLR-low was significantly longer than that of patients with -high (median, 12.6 vs. 7.2 months; hazard ratio (HR), 0.48, 95% confidence interval (95% CI), 0.31–0.73; p = 0.0004). OS of patients with NLR-low was significantly better than those with-high (22.2 vs. 13.5 months; HR, 0.57, 95% CI, 0.39–0.83; p = 0.0032). Similarly, improved PFS and OS were recognized in patients with CRP-low as compared with patients with -high (HR, 0.44, 95% CI, 0.28–0.68; p = 0.0001 and HR, 0.39, 95% CI, 0.26–0.61, p < 0.0001, respectively). In the validation cohort from two institutes (n = 57), similar significant improvements in PFS and OS were confirmed for patients with NLR-low (p = 0.0344 and p = 0.0233, respectively) and CRP-low groups (p < 0.0001 and p = 0.0001, respectively). Low levels of NLR and CRP at baseline were significantly associated with improved prognosis in patients treated with bevacizumab plus paclitaxel.